VALIDASI, DISTRIBUSI DAN PEMANFAATAN ACANTHACEAE DI JAWA - Deden Girmansyah (Research Center for Biology-Indonesian Institute of Sciences, 2014)
Acanthaceae published in Flora of Java has had significant change especially for nomenclature, distribution and potential uses; thus it affected species names of collections of Acanthaceae in Herbarium Bogoriense of The Indonesian Institute of Sciences. It is therefore necessary to update information of Acanthaceae by conducting herbarium and field surveys as well as reviewing related publications. Validation of the species name, synonymous and distribution were carried out by using some online websites such as IPNI, Tropicos and The plantlist. Meanwhile, the potential uses were obtained from several publications. Examinations on herbarium specimens was conducted in the Herbarium Bogoriense, while field survey was carried out in several locations in Java. This study recorded a total of 164 species of Achantaceeae to which 53 were native in Java (Indonesia), 24 species become synonymous, and five other species have not been published. Some of them have potential chemical substances and uses.